Addressing Linguistic Diversity in the Language Classroom in a Resource‐Oriented Way: An Intervention Study With Primary School Children. Issue 2 (29th November 2019) - Busse, Vera; Cenoz, Jasone; Dalmann, Nina; Rogge, Franziska
Abstract: Adequately responding to linguistic diversity in the classroom is imperative in European school contexts, not least because of current migratory movements. This article presents the results of an intervention study with primary school English‐foreign‐language learners in Germany ( N = 42, M age = 8.70 years) from linguistically diverse backgrounds, who participated in a learning unit on the human body (five 45‐minute lessons). Drawing on multilingual education and second language motivational research, we encouraged children in the intervention group to use their linguistic resources, and they engaged with two affective‐experiential activities aimed at stimulating attitudinal aspects of learning. We investigated intervention effects through pre‐, post‐, and follow‐up tests. We measured affect after each lesson. The intervention group displayed higher plurilingual ideal self aspirations after the intervention and higher positive affect throughout the intervention. Importantly, the intervention group made significantly larger vocabulary learning gains than the control group despite spending less time on task. Abstract :